A barc resin, a method of preparation and use thereof
Patent Information
- Application Number
- CN202611064159.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-10-09
AI Technical Summary
BARC树脂多采用苯乙烯类单体与含羟基甲基丙烯酸酯单体二元共聚制备,此类树脂存在以下问题:与半导体基底黏附力不足、刻蚀去除效率低,成膜后易出现针孔、裂纹等缺陷,难以适配先进半导体制程的高精度需求
[0007]与现有技术相比,本发明的BARC树脂的制备方法采用三类不同单体,具体为苯乙烯衍生物单体、含羟基的甲基丙烯酸酯单体和含富氧基的甲基丙烯酸酯单体。根据三类单体不同的物理和化学性质,选择不同极性的多种溶剂混合的复合分散体系,使三类单体在其中能充分溶解并分散均匀。同时,采用不同的投料以及分段控温的方式,进而使三类单体能更均匀、更充分地进行共聚反应,获得分子量分布更窄、性能更稳定的树脂。将该树脂应用于193 nm光刻胶制备BARC,有效改善光刻胶的图案分辨率和线宽粗糙度。
Smart Images

Figure CN122878488A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of semiconductor technology, and in particular to a BARC resin, its preparation method, and its uses. Background Technology
[0002] Bottom Anti-Reflection Coating (BARC) is a crucial functional thin film coated between the silicon substrate and the photoresist in semiconductor photolithography. Its core function is to eliminate interference from substrate-reflected light, ensuring high-precision transfer of fine patterns. Especially in 193 nm deep ultraviolet lithography, BARC absorbs incident light, suppresses substrate reflection, and thus eliminates standing wave effects. This directly affects the resolution and edge quality of the lithographic pattern, making it a critical step in ensuring the precision of semiconductor chip fabrication.
[0003] Currently, organic BARC resins are widely used in semiconductor chip manufacturing due to their excellent film-forming properties and strong compatibility with photolithography processes. Their core component is a polymeric resin containing aromatic rings, which can efficiently absorb deep ultraviolet light at a wavelength of 193 nm, solving the technical problem of uneven photolithography exposure. BARC resins are mostly prepared by binary copolymerization of styrene monomers and hydroxymethyl acrylate monomers. These resins have the following problems: insufficient adhesion to semiconductor substrates, low etching removal efficiency, and susceptibility to defects such as pinholes and cracks after film formation, making them unsuitable for the high-precision requirements of advanced semiconductor processes. To optimize the performance of BARC resins, researchers have attempted to introduce other types of monomers, copolymerizing them with styrene monomers and hydroxymethyl acrylate monomers. However, different monomers exhibit significant differences in chemical reactivity and temperature sensitivity, making it difficult to achieve uniform copolymerization of three or more monomers to obtain an ideal BARC resin. Summary of the Invention
[0004] To address the aforementioned technical problems, this invention provides a BARC resin, its preparation method, and its applications. This preparation method is suitable for copolymerizing three or more monomers, ensuring a uniform and complete polymerization reaction to obtain an ideal BARC resin. Using this BARC resin in the preparation of 193 nm photoresist can better eliminate the standing wave effect and effectively improve the pattern resolution and linewidth roughness of the photoresist.
[0005] This invention provides a method for preparing BARC resin, the method comprising: S1. Mix multiple solvents of different polarities to obtain a composite dispersion system; S2. Take styrene derivative monomers, hydroxyl-containing methacrylate monomers, and oxygen-rich methacrylate monomers, and add them to the composite dispersion system using different feeding methods according to the differences in the reactivity of the three monomers to obtain a prepolymerized liquid. S3. Using a segmented temperature control method and adding an initiator, the prepolymer liquid is allowed to react fully to obtain a polymerization reaction liquid; S4. The polymerization reaction solution is subjected to precipitation treatment to separate the precipitate and obtain the BARC resin.
[0006] The present invention also provides a BARC resin obtained by the aforementioned method for preparing BARC resin and its use in the preparation of 193 nm deep ultraviolet photoresist.
[0007] Compared with existing technologies, the preparation method of BARC resin in this invention uses three different types of monomers: styrene derivative monomers, hydroxyl-containing methacrylate monomers, and oxygen-rich methacrylate monomers. Based on the different physical and chemical properties of the three types of monomers, a composite dispersion system using multiple solvents of different polarities is selected to ensure that the three types of monomers are fully dissolved and uniformly dispersed. Simultaneously, different feeding methods and segmented temperature control are employed to allow the three types of monomers to undergo a more uniform and complete copolymerization reaction, resulting in a resin with a narrower molecular weight distribution and more stable performance. When this resin is applied to the preparation of BARC using 193 nm photoresist, it effectively improves the pattern resolution and linewidth roughness of the photoresist. Attached Figure Description
[0008] Figure 1 This is the 193 nm deep ultraviolet photoresist line image corresponding to Example 1; Figure 2 This is the 193 nm deep ultraviolet photoresist line image corresponding to Example 2; Figure 3 This is the 193 nm deep ultraviolet photoresist line image corresponding to Example 3; Figure 4 This is the 193 nm deep ultraviolet photoresist line image corresponding to Example 4; Figure 5 This is the 193 nm deep ultraviolet photoresist line image corresponding to Example 5; Figure 6 This is a 193 nm deep ultraviolet photoresist line image corresponding to Comparative Example 1; Figure 7 This is a line image of the 193 nm deep ultraviolet photoresist corresponding to Comparative Example 2. Detailed Implementation
[0009] To better explain the present invention, the present invention will be further described in detail below with reference to specific embodiments. These embodiments are not intended to limit the present invention.
[0010] Research on optimizing resin properties has revealed that adding oxygen-rich methacrylate monomers to styrene-based monomers and hydroxyl-containing methacrylate monomers for ternary copolymerization can leverage the strong adhesion and compatibility of oxygen-rich functional groups to improve the bonding force between the resin and the substrate and the film density. This addresses the issues of insufficient adhesion and low etching removal efficiency in resins prepared from binary copolymer monomers. However, the three types of monomers exhibit significant differences in reactivity and sensitivity to reaction temperature. Styrene derivative monomers are highly reactive and can polymerize rapidly at low temperatures; hydroxyl-containing methacrylate monomers have moderate reactivity and require suitable temperatures to maintain polymerization; and oxygen-rich methacrylate monomers have low reactivity. Therefore, traditional preparation processes (i.e., one-time feeding and isothermal polymerization) struggle to achieve uniform copolymerization of the three types of monomers. This results in a wide molecular weight distribution and unstable performance in the obtained resin, and unreacted monomer residues can cause film defects, increasing the edge roughness (LWR) of the lithographic pattern, thus failing to meet the high precision requirements of advanced semiconductor processes. Furthermore, the existing process uses a single solvent reaction system with fixed polarity, which makes it difficult to adapt to the solubility characteristics of the three types of monomers, further exacerbating the problem of uneven copolymerization.
[0011] In response to the above situation, after extensive research, a method for preparing BARC resin according to the present invention was unexpectedly obtained, the preparation method comprising: S1. Mix multiple solvents of different polarities to obtain a composite dispersion system; S2. Take styrene derivative monomers, hydroxyl-containing methacrylate monomers, and oxygen-rich methacrylate monomers, and add them to the composite dispersion system using different feeding methods according to the differences in the reactivity of the three monomers to obtain a prepolymerized liquid. S3. Using a segmented temperature control method and adding an initiator, the prepolymer liquid is allowed to react fully to obtain a polymerization reaction liquid; S4. The polymerization reaction solution is subjected to precipitation treatment to separate the precipitate and obtain the BARC resin.
[0012] To address the differences in solubility, reactivity, and temperature sensitivity among the three monomer types, the preparation method of the BARC resin in this invention employs a mixed dispersion system with multiple solvents (S1), a segmented differentiated feeding strategy (S2), and a segmented temperature-controlled polymerization strategy (S3). The composite dispersion system obtained by mixing multiple solvents of different polarities is suitable for the complete dissolution of the three monomer types and subsequent polymerization reactions. The segmented differentiated feeding strategy is based on the reactivity gradient of the three monomers (styrene derivatives > hydroxyl-containing methacrylates > oxygen-rich methacrylates), employing a targeted feeding method to ensure sufficient contact and polymerization of various monomers in the reaction system. The segmented temperature-controlled polymerization strategy generally involves controlling the reaction temperature in two stages. The first stage is a low-temperature initiation stage, adapting to the low-temperature polymerization characteristics of styrene derivative monomers to slowly initiate polymerization and avoid excessively vigorous reactions leading to uneven monomer copolymerization. The second stage is a heating and holding stage to increase the polymerization rate of hydroxyl-containing methacrylates and oxygen-rich methacrylate monomers. Simultaneously, by adding initiators, it ensures sufficient copolymerization of the three monomers and further narrows the molecular weight distribution of the resin. Of course, the reaction temperature can also be controlled in three or even four stages depending on the specific reaction conditions. The combination of a mixed dispersion system of multiple solvents (S1), a segmented differentiated feeding strategy (S2), and a segmented temperature-controlled polymerization strategy (S3) ensures the full copolymerization of the three types of monomers, resulting in a BARC resin with a narrower molecular weight distribution and more stable performance.
[0013] In some embodiments, the multiple solvents with different polarities are two organic solvents with a polarity parameter difference greater than 1. Here, the polarity parameter is a numerical value used to score the strength of solvent polarity, such as dielectric constant, dipole moment, ET (30) value, n-octanol-water partition coefficient (logP), Snyder polarity index, etc. The larger the polarity parameter, the stronger the polarity of the solvent. As an example, a polarity parameter difference greater than 1 means that the difference in Snyder polarity index between the two organic solvents is greater than 1. When other parameters are used to score the strength of solvent polarity, corresponding adjustments can be made, and the corresponding adjustment scheme should also fall within the scope of this invention. Here, a polarity parameter difference (Snyder polarity index difference) greater than 1 indicates that the polarity difference between the two solvents is relatively large, and a gradient difference can be made. More preferably, the polarity difference between the two solvents should not be too large, as a large difference may interfere with the subsequent polymerization reaction. Preferably, the polarity parameter difference between the two organic solvents is greater than 1 and less than 3. It should be noted that the polarity parameter difference greater than 1 is based on extensive experimental data, indicating a certain difference in polarity between the two organic solvents. This allows the mixture to dissolve monomers of different polarities, satisfying the dissolution requirements of styrene derivative monomers, hydroxyl-containing methacrylate monomers, and oxygen-rich methacrylate monomers. Of course, adjustments to the structures of the three monomers may affect their solubility, necessitating corresponding adjustments to the composition of the composite dispersion system. In rare cases, the polarity parameter difference between the two organic solvents may be less than 1.
[0014] Preferably, the two organic solvents are selected from the following organic solvents: cyclohexanone, ethylene glycol methyl ether, butyl propionate, diethylene glycol ethyl ether, and amyl acetate.
[0015] In some embodiments, the polarity parameter of the composite dispersion system is 4.5-6.5 (here, the polarity parameter is characterized by the Snyder polarity index). This polarity composite dispersion system is particularly suitable for three types of monomers: styrene derivative monomers, hydroxyl-containing methacrylate monomers, and oxygen-rich methacrylate monomers, as well as their polymers, satisfying the solubility characteristics of these three types of monomers and their polymers. Similarly, the polarity parameter here is calculated based on the polarity parameter (here characterized by the Snyder polarity index, but other parameters can also be used with appropriate conversion) and their weight ratio in the composite dispersion system. For example, the Snyder polarity index of cyclohexanone (refer to Snyder, LR; 'Classification of the Solvent Properties of Common Liquids', J. Chromatography, 92 (1978) 223-234.) is 4.5, and the Snyder polarity index of ethylene glycol methyl ether is 5.7. Therefore, the polarity parameter of the composite dispersion system obtained by mixing cyclohexanone and ethylene glycol methyl ether at a weight ratio of 1:1 is (4.5*1+5.7*1) / (1+1)=5.1.
[0016] Preferably, the mixing of multiple solvents with different polarities specifically involves mixing cyclohexanone and ethylene glycol methyl ether in a weight ratio of 2-8:2-8. This ratio allows the polarity of the system to be precisely controlled between 4.5 and 6.5, adapting to the dissolution and polymerization requirements of the three monomers.
[0017] In some embodiments, the styrene derivative monomer is selected from at least one of p-tert-butylstyrene and p-fluorostyrene. The styrene derivative monomer introduces an aromatic ring structure, which efficiently absorbs deep ultraviolet light at a wavelength of 193 nm, exerting an anti-reflective effect while simultaneously improving the resin's thermal stability and etching resistance.
[0018] In some embodiments, the hydroxyl-containing methacrylate monomer is selected from at least one of hydroxypropyl methacrylate and hydroxyethyl methacrylate. The hydroxyl groups in the hydroxyl-containing methacrylate monomer enhance the adhesion between the resin and the substrate, optimize the film density of the resin, and enable it to undergo crosslinking reactions with crosslinking agents when used in the later stages.
[0019] In some embodiments, the oxygen-rich monomer is selected from at least one of methoxyethyl methacrylate and methoxyethoxyethyl methacrylate. The oxygen-rich monomer can further enhance the adhesion between the resin and the semiconductor substrate, while improving the resin's corrosion resistance and process compatibility, and reducing film formation defects.
[0020] In some embodiments, the addition of different feeding methods to the composite dispersion system based on the differences in reactivity of the three monomers includes: adding the styrene derivative monomer to the composite dispersion system in 2-3 batches; adding the hydroxyl-containing methacrylate monomer to the composite dispersion system at a constant temperature and rate; and adding the oxygen-rich methacrylate monomer to the composite dispersion system at a constant temperature and variable rate. Specifically, while adding the first batch of styrene derivative monomer, the hydroxyl-containing methacrylate monomer and the oxygen-rich methacrylate monomer are added dropwise to initiate the reaction. Subsequently, the hydroxyl-containing methacrylate monomer is added dropwise at a constant temperature and rate, the oxygen-rich methacrylate monomer is added dropwise at a constant temperature and variable rate, and a second batch or a second batch plus a third batch of styrene derivative monomer is added.
[0021] In some embodiments, the hydroxyl-containing acrylate monomer is dropped at a rate of 0.6 mL / min - 2.0 mL / min, with a dropping time of 45 min - 75 min; the oxygen-rich monomer is initially dropped at a rate of 1.4 mL / min - 3.0 mL / min, which gradually decreases to 0.9 mL / min - 1.6 mL / min after 14 min - 20 min, with a total dropping time of 30 min - 50 min.
[0022] In some embodiments, the weight ratio of the styrene derivative monomer, the hydroxyl-containing methacrylate monomer, the oxygen-rich methacrylate monomer, and the composite dispersion system in the prepolymer solution is 3-4 : 2-3 : 5-6 : 95-115. Preferably, the styrene derivative monomer is p-tert-butylstyrene, the hydroxyl-containing methacrylate monomer is hydroxyethyl methacrylate, and the oxygen-rich methacrylate monomer is methoxyethyl methacrylate. This ratio optimizes the copolymerization effect of the three monomers, ensuring a balance in the resin's antireflective properties, adhesion properties, and etching properties.
[0023] In some embodiments, the step of using segmented temperature control and adding an initiator to ensure the prepolymer solution reacts fully includes: first heating the prepolymer solution to 55℃-65℃ to initiate polymerization for 1.5 h-2.5 h, then heating it to 75℃-85℃ and holding it at that temperature for copolymerization for 20 h-24 h, with the initiator added in 1-2 stages during this period. Adding the initiator helps maintain a stable free radical concentration in the system, further narrows the resin molecular weight distribution, and improves the resin's performance stability.
[0024] In some embodiments, the initiator is at least one of azobisisovalerate, azobisisobutyramide, benzoyl peroxide tert-butyl ester, and benzoyl peroxide; the initial amount is 0.8% - 1.8% of the total weight of the monomer, and the amount of additional initiator is 30% - 50% of the initial amount.
[0025] In some embodiments, step S4, which involves precipitating the polymerization reaction solution to separate the precipitate and obtain the BARC resin, specifically involves: cooling the polymerization reaction solution to room temperature, and first performing vacuum distillation at 70℃-80℃ and 0.06 MPa-0.08 MPa to remove excess reaction solvent and low-boiling-point impurities from the system; then, adding the distilled polymerization reaction solution dropwise to a mixed washing solution of ethanol and n-heptane (volume ratio 1:3-1:5) for precipitation and purification, with the volume of the mixed washing solution being 10-14 times that of the polymerization reaction solution; after solid-liquid separation, washing the precipitate 2-3 times with the above mixed washing solution, and then drying the precipitate in a vacuum oven at 85℃-95℃ for 5-7 hours to obtain high-purity BARC resin. The combination of vacuum distillation and mixed washing solution precipitation can thoroughly remove unreacted monomers and impurities, further improving the resin purity and performance stability.
[0026] In some embodiments of the present invention, a BARC resin is provided, which is obtained by the aforementioned method for preparing BARC resin. This BARC resin has a narrow weight-average molecular weight distribution (polymer dispersibility index PDI is reduced by 22%-38% compared to conventional processes), strong adhesion to the substrate, and forms a dense, defect-free film.
[0027] In some embodiments of the present invention, the use of the aforementioned BARC resin in the preparation of 193 nm deep ultraviolet photoresist is provided. When the BARC resin is used to prepare BARC, the BARC film exhibits good thickness uniformity, efficient absorption of 193 nm wavelength deep ultraviolet light, and excellent anti-reflection properties, thereby reducing the edge roughness (LWR) of the photoresist pattern, improving the resolution of the photolithographic pattern, and meeting the high-precision application requirements of advanced semiconductor processes.
[0028] In some embodiments, the use of the aforementioned BARC resin in the preparation of 193 nm deep ultraviolet photoresist includes: using the BARC resin to prepare photoresist BARC; the specific process includes: mixing the BARC resin with a crosslinking agent, a thermogenic acid-producing agent, and a solvent uniformly; after filtration and degassing treatment, spin-coating it onto a silicon wafer substrate; and obtaining BARC by baking at 90℃-110℃ for 30 s-60 s and developing.
[0029] The following are specific examples, comparative examples, and related experimental data, which are used to illustrate the effects of the present invention and to better explain the present invention.
[0030] Example 1 1. Preparation of the composite dispersion system: Cyclohexanone and ethylene glycol methyl ether were mixed evenly at a weight ratio of 5:5. The polarity parameter, characterized by the Snyder polarity index, was 5.1.
[0031] 2. Preparation of prepolymer solution: p-tert-butylstyrene, hydroxypropyl methacrylate, methoxyethoxyethyl methacrylate, and a composite dispersion system were prepared in a weight ratio of 3.5:2.5:5.5:105. p-tert-butylstyrene was added in two batches to a four-necked flask containing the composite dispersion system (20 min interval between the two additions), and the mixture was stirred until homogeneous. Hydroxypropyl methacrylate was added dropwise to the flask at a constant rate of 0.9 mL / min under constant temperature of 42 °C for 52 min. Methoxyethoxyethyl methacrylate was added dropwise at an initial rate of 1.9 mL / min under constant temperature of 42 °C, decreasing to 1.1 mL / min after 17 min, for a total addition time of 37 min. After the addition was complete, stirring was continued for 35 min to ensure homogeneous monomer mixing, yielding the prepolymer solution.
[0032] 3. Segmented temperature-controlled polymerization: Add azobisisovalerate (initial amount is 1.1% of the total monomer) to the prepolymer solution and stir until dissolved. Place a four-necked flask in an oil bath, purge with nitrogen, turn on the cooling water, first raise the temperature to 60 ℃, and hold at this temperature for 2 h to initiate polymerization; then raise the temperature to 80 ℃ and hold at this temperature for copolymerization for 22 h. During this period, add the initiator solution once every 10 h (the amount added is 40% of the initial amount) to obtain the polymerization reaction solution.
[0033] 4. Post-treatment: Cool the polymerization reaction solution to room temperature and remove impurities by vacuum distillation at 75 ℃ and 0.07 MPa. Add the distilled reaction solution dropwise to a mixed washing solution of 12 times the volume of ethanol and n-heptane (volume ratio 1:4) to precipitate. After solid-liquid separation, wash the precipitate twice with the mixed washing solution and dry it in a vacuum oven at 90 ℃ for 6 h to obtain BARC resin.
[0034] Example 2 1. Preparation of the composite dispersion system: Cyclohexanone and ethylene glycol methyl ether were mixed evenly at a weight ratio of 6:4. The polarity parameter, characterized by the Snyder polarity index, was 4.98.
[0035] 2. Preparation of the prepolymer solution: p-tert-butylstyrene, hydroxypropyl methacrylate, methoxyethoxyethyl methacrylate, and a composite dispersion system were prepared according to a weight ratio of 3.7:2.3:5.3:110. p-tert-butylstyrene was added in two batches to a four-necked flask containing the composite dispersion system (with a 20-minute interval between the two additions), and the mixture was stirred until homogeneous. Hydroxypropyl methacrylate was added dropwise to the flask at a constant rate of 1.1 mL / min under constant temperature (42 °C) for 48 min. Methoxyethoxyethyl methacrylate was added dropwise at an initial rate of 2.1 mL / min under constant temperature (42 °C), decreasing to 1.3 mL / min after 15 min, for a total addition time of 34 min. After the addition was complete, stirring was continued for 35 min to obtain the prepolymer solution.
[0036] 3. Segmented temperature-controlled polymerization: Add azobisisovalerate (initial amount is 1.1% of the total monomer) to the prepolymer solution and stir until dissolved. Place a four-necked flask in an oil bath, purge with nitrogen, turn on the cooling water, first raise the temperature to 62 ℃, and hold at this temperature for 1.8 h to initiate polymerization; then raise the temperature to 82 ℃ and hold at this temperature for copolymerization for 21 h. During this period, add the initiator solution once every 10 h (the amount added is 40% of the initial amount) to obtain the polymerization reaction solution.
[0037] 4. Post-processing: Same as in Example 1, to obtain BARC resin.
[0038] Example 3 1. Preparation of the composite dispersion system: Cyclohexanone and ethylene glycol methyl ether were mixed evenly at a weight ratio of 4:6. The polarity parameter, characterized by the Snyder polarity index, was 5.22.
[0039] 2. Preparation of the prepolymer solution: p-tert-butylstyrene, hydroxypropyl methacrylate, methoxyethoxyethyl methacrylate, and a composite dispersion system were prepared in a weight ratio of 3.3:2.7:5.7:100. p-tert-butylstyrene was added in two batches to a four-necked flask containing the composite dispersion system (20 min interval between the two additions), and the mixture was stirred until homogeneous. Hydroxypropyl methacrylate was added dropwise to the flask at a constant rate of 1.3 mL / min under constant temperature of 42 °C for 44 min. Methoxyethoxyethyl methacrylate was added dropwise at an initial rate of 2.3 mL / min under constant temperature of 42 °C, decreasing to 1.5 mL / min after 18 min, for a total addition time of 40 min. After the addition was complete, stirring was continued for 35 min to obtain the prepolymer solution.
[0040] 3. Segmented temperature-controlled polymerization: Add azobisisovalerate (initial amount is 1.1% of the total monomer) to the prepolymer solution and stir until dissolved. Place a four-necked flask in an oil bath, purge with nitrogen, turn on the cooling water, first raise the temperature to 58 ℃, and hold at this temperature for 2.2 h to initiate polymerization; then raise the temperature to 78 ℃ and hold at this temperature for copolymerization for 23 h. During this period, add the initiator solution once every 10 h (the amount added is 40% of the initial amount) to obtain the polymerization reaction solution.
[0041] 4. Post-processing: Same as in Example 1, to obtain BARC resin.
[0042] Example 4 1. Preparation of the composite dispersion system: Cyclohexanone and ethylene glycol methyl ether were mixed evenly at a weight ratio of 7:3. The polarity parameter, characterized by the Snyder polarity index, was 4.86.
[0043] 2. Preparation of the prepolymer solution: p-tert-butylstyrene, hydroxypropyl methacrylate, methoxyethoxyethyl methacrylate, and a composite dispersion system were prepared according to a weight ratio of 3.8:2.2:5.2:112. p-tert-butylstyrene was added in three batches to a four-necked flask containing the composite dispersion system (each batch added 15 min apart), and stirred until uniformly dispersed. Hydroxypropyl methacrylate was added dropwise to the flask at a constant rate of 1.5 mL / min under constant temperature of 42 °C for 40 min. Methoxyethoxyethyl methacrylate was added dropwise at an initial rate of 2.5 mL / min under constant temperature of 42 °C, decreasing to 1.4 mL / min after 16 min, for a total addition time of 32 min. After the addition was complete, stirring was continued for 35 min to obtain the prepolymer solution.
[0044] 3. Segmented temperature-controlled polymerization: Add azobisisovalerate (initial amount is 1.1% of the total monomer) to the prepolymer solution and stir until dissolved. Place a four-necked flask in an oil bath, purge with nitrogen and turn on the cooling water, first raise the temperature to 63 ℃ and hold at that temperature for 1.7 h to initiate polymerization; then raise the temperature to 83 ℃ and hold at that temperature for 20 h to copolymerize, during which the initiator solution is added twice (each addition is 20% of the initial amount, added at 8 h and 16 h of holding time) to obtain the polymerization reaction solution.
[0045] 4. Post-processing: Same as in Example 1, to obtain BARC resin.
[0046] Example 5 1. Preparation of the composite dispersion system: Cyclohexanone and ethylene glycol methyl ether were mixed evenly at a weight ratio of 3:7. The polarity parameter, characterized by the Snyder polarity index, was 5.34.
[0047] 2. Preparation of prepolymer solution: p-tert-butylstyrene, hydroxypropyl methacrylate, methoxyethoxyethyl methacrylate, and a composite dispersion system were prepared in a weight ratio of 3.2:2.8:5.8:98. p-tert-butylstyrene was added in three batches to a four-necked flask containing the composite dispersion system (each batch added 15 min apart), and stirred until uniformly dispersed. Hydroxypropyl methacrylate was added dropwise to the flask at a constant rate of 0.7 mL / min under constant temperature of 42 °C for 58 min. Methoxyethoxyethyl methacrylate was added dropwise at an initial rate of 1.6 mL / min under constant temperature of 42 °C, decreasing to 0.9 mL / min after 19 min, for a total addition time of 43 min. After the addition was complete, stirring was continued for 35 min to obtain the prepolymer solution.
[0048] 3. Segmented temperature-controlled polymerization: Add azobisisovalerate (initial amount is 1.1% of the total monomer) to the prepolymer solution and stir until dissolved. Place a four-necked flask in an oil bath, purge with nitrogen, turn on the cooling water, first raise the temperature to 56 ℃, and hold at this temperature for 2.3 h to initiate polymerization; then raise the temperature to 76 ℃ and hold at this temperature for copolymerization for 24 h, during which the initiator solution is added twice (each addition is 20% of the initial amount, added at 8 h and 16 h of holding time) to obtain the polymerization reaction solution.
[0049] 4. Post-processing: Same as in Example 1, to obtain BARC resin.
[0050] Comparative Example 1 It employs constant temperature conditions, one-time feeding, and a single solvent.
[0051] 1. Solvent preparation: Cyclohexanone was selected as the single solvent with a polarity parameter of 4.5.
[0052] 2. Preparation of prepolymer solution: Take p-tert-butylstyrene, hydroxypropyl methacrylate, methoxyethoxyethyl methacrylate, and cyclohexanone in a weight ratio of 3.5:2.5:5.5:105. Add the three monomers at once to a four-necked flask containing solvent and stir until homogeneous.
[0053] 3. Polymerization reaction: Add azobisisovalerate (1.1% of the total monomer amount) to the prepolymer solution and stir until dissolved. Place a four-necked flask in an oil bath, purge with nitrogen, turn on the cooling water, and reflux at 80 °C for 24 h to obtain the polymerization reaction solution.
[0054] 4. Post-processing: Same as in Example 1, to obtain BARC resin.
[0055] Comparative Example 2 It employs constant temperature conditions, one-time feeding, and composite solvents.
[0056] 1. Solvent preparation: Cyclohexanone and ethylene glycol methyl ether were mixed thoroughly in a weight ratio of 5:5. The polarity parameter, characterized by the Snyder polarity index, was 5.1.
[0057] 2. Preparation of prepolymer solution: Take p-tert-butylstyrene, hydroxypropyl methacrylate, methoxyethoxyethyl methacrylate, and a composite solvent in a weight ratio of 3.5:2.5:5.5:105. Add all three monomers at once to a four-necked flask containing the solvent and stir until homogeneous.
[0058] 3. Polymerization reaction: Add azobisisovalerate (1.1% of the total monomer amount) to the prepolymer solution and stir until dissolved. Place a four-necked flask in an oil bath, purge with nitrogen, turn on the cooling water, and reflux at 80 °C for 24 h to obtain the polymerization reaction solution.
[0059] 4. Post-processing: Same as in Example 1, to obtain BARC resin.
[0060] Performance testing and results analysis The performance of the BARC resins prepared in Examples 1-5 and Comparative Examples 1-2 was tested. The test indicators included: weight-average molecular weight (Mw) and polymer dispersibility index (PDI); after the resin was prepared into BARC, the film thickness uniformity (STDEV) was tested; and the linewidth roughness (LWR) was tested when BARC was applied to a 193 nm deep ultraviolet photoresist. The test results are shown in the table below.
[0061] Table 1
[0062] Based on the above test results, we can conclude that: 1. Resin Uniformity: The PDI values of the BARC resins prepared in Examples 1 to 5 were all less than 1.5, significantly lower than those of Comparative Example 1 (2.35) and Comparative Example 2 (2.87). This fully demonstrates that the BARC resin preparation method of the present invention can effectively balance the polymerization rates of the three monomers, solve the technical problem of uneven copolymerization, and obtain resins with narrower molecular weight distribution and more stable performance.
[0063] 2. Application Performance: The BARC film thickness uniformity STDEV values prepared from the BARC resins of Examples 1 to 5 were 1.3–2.2, significantly better than those of Comparative Example 1 (24.6) and Comparative Example 2 (35.2); the corresponding photoresist LWR values were 3.88–6.29, significantly lower than those of Comparative Example 1 (9.44) and Comparative Example 2 (11.23). Furthermore, the 193 nm deep ultraviolet photoresist line patterns corresponding to Examples 1 to 5 are as follows... Figures 1 to 5As shown, the 193 nm deep ultraviolet photoresist line patterns corresponding to Comparative Example 1 and Comparative Example 2 are respectively as follows: Figure 6 and Figure 7 As shown, the lines in the embodiment are significantly clearer. Therefore, using the BARC resin of this invention in the preparation of BARC for 193nm deep ultraviolet photoresist can effectively improve the pattern resolution and linewidth roughness of the photoresist.
[0064] In summary, the BARC resin preparation method of this invention employs a segmented differentiated feeding strategy and a segmented temperature-controlled polymerization strategy, combined with a polarity-adjustable composite dispersion system, effectively solving the technical pain points of uneven copolymerization of the three types of monomers, numerous film-forming defects, and unstable performance. A BARC resin with narrow molecular weight distribution, good adhesion, and excellent anti-reflection properties was successfully obtained. When this BARC resin is used in the preparation of 193 nm deep ultraviolet photoresist, it can significantly improve photolithography performance. Furthermore, the process is simple, highly controllable, and easy to scale up for mass production, possessing significant industrial application value.
[0065] It should be noted that the present invention is not limited to the above embodiments. The monomers, solvents and initiators described in the embodiments are only examples and are not intended to limit the scope of the examples. Any conventional substitutions and adjustments to the technical features based on the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing BARC resin, characterized in that, The preparation method includes: S1. Mix multiple solvents of different polarities to obtain a composite dispersion system; S2. Take styrene derivative monomers, hydroxyl-containing methacrylate monomers, and oxygen-rich methacrylate monomers, and add them to the composite dispersion system using different feeding methods according to the differences in the reactivity of the three monomers to obtain a prepolymerized liquid. S3. Using a segmented temperature control method and adding an initiator, the prepolymer liquid is allowed to react fully to obtain a polymerization reaction liquid; S4. The polymerization reaction solution is subjected to precipitation treatment to separate the precipitate and obtain the BARC resin.
2. The preparation method according to claim 1, characterized in that, The various solvents with different polarities are two organic solvents with a polarity parameter difference greater than 1; the two organic solvents are selected from the following organic solvents: cyclohexanone, ethylene glycol methyl ether, butyl propionate, diethylene glycol ethyl ether, and amyl acetate.
3. The preparation method according to claim 2, characterized in that, The mixing of multiple solvents with different polarities specifically involves mixing cyclohexanone and ethylene glycol methyl ether in a weight ratio of 2-8:2-8; the polarity parameter of the composite dispersion system is 4.5-6.
5.
4. The preparation method according to claim 1, characterized in that, The styrene derivative monomer is selected from at least one of p-tert-butylstyrene and p-fluorostyrene; the hydroxyl-containing methacrylate monomer is selected from at least one of hydroxypropyl methacrylate and hydroxyethyl methacrylate; the oxygen-rich monomer is selected from at least one of methoxyethyl methacrylate and methoxyethoxyethyl methacrylate.
5. The preparation method according to claim 1, characterized in that, The method of adding the three monomers into the composite dispersion system using different feeding methods based on their different reactivity includes: adding the styrene derivative monomers into the composite dispersion system in 2-3 batches; adding the hydroxyl-containing methacrylate monomers to the composite dispersion system at a constant temperature and rate; and adding the oxygen-rich methacrylate monomers to the composite dispersion system at a constant temperature and variable rate.
6. The preparation method according to claim 5, characterized in that, The hydroxyl-containing acrylate monomer was added at a dropping rate of 0.6 mL / min - 2.0 mL / min over a dropping time of 45 min - 75 min. The oxygen-rich monomer was added at an initial dropping rate of 1.4 mL / min - 3.0 mL / min, which gradually decreased to 0.9 mL / min - 1.6 mL / min after 14 min - 20 min, with a total dropping time of 30 min - 50 min.
7. The preparation method according to claim 1, characterized in that, The weight ratio of styrene derivative monomers, hydroxyl-containing methacrylate monomers, oxygen-rich methacrylate monomers, and the composite dispersion system in the prepolymer liquid is 3-4 : 2-3 : 5-6 : 95-115.
8. The preparation method according to claim 1, characterized in that, The method of using segmented temperature control and adding initiators to ensure the full reaction of the prepolymer liquid includes: first heating the prepolymer liquid to 55 ℃ - 65 ℃ to initiate polymerization for 1.5 h - 2.5 h, then heating it to 75 ℃ - 85 ℃ and holding it at that temperature for copolymerization for 20 h - 24 h, during which time the initiator is added 1 - 2 times.
9. A BARC resin, characterized in that, Obtained by the preparation method described in any one of claims 1-8.
10. Use of the BARC resin as described in claim 9 in the preparation of 193 nm deep ultraviolet photoresist.